If you were there in 1776 - Brenner, Barbara (Simon & Schuster, 1994)
Demonstrates how the concepts and principles expressed in the Declaration of Independence were drawn from the experiences of living in America in the late eighteenth century, with emphasis given to how children lived on a New England farm, a Southern plantation, and the frontier